In-situ repair silicon-based composite material and preparation method thereof
By using repairing agents such as epoxy silanes on silicon-based materials for in-situ modification and low-temperature carbonization treatment, silicone-carbon repair patches are formed, solving the problems of carbon cladding damage and slurry instability caused by prelithiation. , improves the circulation performance and stability of the negative electrode of lithium battery.
Patent Information
- Application Number
- CN202411320219.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
In the prior art, the carbon coating layer of silicon-based materials is damaged during prelithiation, resulting in deterioration of the stability of the negative electrode slurry and degradation of the electrochemical performance of the battery, and the silicon grains increase during the secondary carbon coating, which affects the Long cycle properties of the material.
The prelithiated carbon-containing clad silicon-based material is modified in situ by using a composite repair agent composed of epoxy silane, bisaminosilane, bisilane polyethylene glycol and 1,3,5-benzene tricarboxylic chloride, and Through low-temperature carbonization treatment, dense silicone-carbon repair patches are formed to inhibit lithium silicate dissolution and gas production of slurry.
It effectively inhibits the dissolution of lithium silicate and gelation of slurry, avoids gas production of slurry, maintains the size of silicon grains, and improves the stability of the negative electrode material and the circulation performance of the battery.
Smart Images

Figure CN119208558A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to an in-situ repaired silicon-based composite material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are one of the most attractive energy storage devices at present because of their high energy density, long life, and environmental friendliness. In lithium batteries, compared with traditional graphite negative electrodes, silicon-based negative electrode materials have attracted much attention due to their higher specific capacity, but the volume expansion of pure silicon negative electrodes during the charging and discharging process is too large, which leads to problems such as material pulverization, and therefore cannot meet the long cycle requirements. Compared with pure silicon negative electrodes, silicon-based oxide negative electrode materials generate irreversible inert components such as lithium oxide and lithium silicate during the first lithium insertion process due to the introduction of oxygen. They alleviate the volume expansion during the cycle to a certain extent, thereby improving the cycle stability. However, the generation of irreversible compounds will cause irreversible consumption of lithium ions. In the prior art, this problem is generally improved by pre-lithiation, that is, silicon-based oxides react with lithium in advance to generate lithium silicate, thereby avoiding the irreversible loss of lithium ions during the first charge and discharge. Due to the high activity of silicon-based oxides, direct pre-lithiation will lead to problems such as too fast reaction and material agglomeration. Therefore, silicon-based oxides need to be carbon-coated before pre-lithiation, that is, the silicon-based oxides are first carbon-coated and then pre-lithiation. However, during the pre-lithiation process, the silicon-based material containing the carbon coating layer will expand to a certain extent, thereby damaging the integrity of the carbon coating layer to a certain extent. At the same time, the residual lithium formed by pre-lithiation and the lithium silicate dissolved at the rupture of the carbon layer will make the material more alkaline, so the slurry formed by the pre-lithiation silicon-based material in the preparation of the negative electrode may undergo gelation; in addition, the silicon-based material with a damaged carbon coating reacts with water under alkaline conditions to produce hydrogen, which leads to gas production in the slurry; that is, the gelation phenomenon and the gas production problem of the slurry lead to poor stability of the negative electrode slurry. In the manufacture of lithium-ion batteries, the negative electrode is prepared by mixing the silicon-based composite material with a conductive agent and an adhesive in a certain proportion to form a slurry. The stability of the slurry is very important for the performance of the negative electrode material and even the battery.
[0003] In the prior art, the problems caused by the above-mentioned pre-lithiation are generally solved by secondary carbon coating through CVD method to construct a repair carbon layer. However, the CVD method often requires a high temperature of more than 700°C to form a highly stable repair carbon layer. At the same time, high temperature will significantly increase the size of silicon grains. Large silicon grains will lead to poor material cycle performance.
[0004] The applicant's previous patent CN116504955A disclosed a highly stable silicon-based negative electrode material and its preparation method and application. The preparation method of the silicon-based negative electrode material includes the following steps: the silicon source is sequentially subjected to a primary carbon coating treatment, pre-lithiation and a secondary carbon coating treatment to obtain the silicon-based negative electrode material; wherein the primary carbon coating temperature is 900-1100°C, and the size of the silicon grains of the primary carbon coating is between 3 and 5 nm; the pre-lithiation sintering temperature is 400-800°C, and the grain size after pre-lithiation is between 5 and 7 nm; the temperature of the CVD method in the secondary carbon coating is 700-800°C, and the size of the silicon grains after treatment is between 6 and 8 nm. This patent effectively improves the stability and initial efficiency of silicon-based negative electrode materials, but the silicon grains increase in size during the secondary carbon coating process, and the long-cycle performance of the negative electrode material is hindered, which needs to be further improved. Summary of the invention
[0005] In order to solve the defects of the above-mentioned prior art that the carbon coating layer caused by the pre-lithiation of silicon-based materials is destroyed, resulting in poor stability of the negative electrode slurry and decreased electrochemical performance of the battery, the present invention pre-lithiates the silicon-based material containing the carbon coating layer, and then uses a composite repair agent composed of epoxysilane, bisaminosilane, disilane polyethylene glycol and 1,3,5-benzenetricarboxylic acid chloride to modify it in situ, and then performs a low-temperature carbonization treatment to form a dense and stable organic silicon-carbon repair patch at the rupture of the carbon layer, thereby inhibiting the dissolution of lithium silicate of the pre-lithiated silicon-based material and avoiding the sedimentation of the negative electrode slurry and the occurrence of gas production; at the same time, the carbonization is carried out at a relatively low temperature, so it will not cause a significant increase in the silicon grains.
[0006] To achieve the above object, the present invention adopts the following scheme:
[0007] An in-situ repaired silicon-based composite material is obtained by in-situ modification of a silicon-based material of a pre-lithiated carbon-containing coating layer with a repair agent, and then carbonization at 450-600°C to form an organic silicon-carbon repair patch; the repair agent is a compound of epoxysilane, bisaminosilane, bissilane polyethylene glycol, and 1,3,5-benzenetricarboxylic acid chloride in a mass ratio of 1: (0.5-0.8): (0.1-0.2): (0.01-0.03); the mass ratio of the silicon-based material of the pre-lithiated carbon-containing coating layer to the repair agent is 100: (7-20).
[0008] Furthermore, the repair agent is a compound of epoxy silane, bisaminosilane, bissilane polyethylene glycol, and 1,3,5-benzenetricarboxylic acid chloride in a mass ratio of 1: (0.6-0.7): (0.15-0.2) (0.02-0.03).
[0009] Furthermore, the mass ratio of the silicon-based material of the pre-lithiation carbon-containing coating layer to the repair agent is 100:(12-16).
[0010] Furthermore, the epoxysilane is at least one of (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)triethoxysilane, (3-glycidoxypropyl)methyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0011] Furthermore, the bisaminosilane is at least one of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, and N-(2-aminoethyl)-3-aminoisobutyldimethylmethoxysilane.
[0012] Furthermore, the number average molecular weight of the polyethylene glycol segment in the disilane polyethylene glycol is 400 to 800, that is, the number average molecular weight of the PEG segment is 400-800. Disilane polyethylene glycol is a long-chain bifunctional silane coupling agent, and its long chain segment can shuttle with short-chain epoxy silane and bisamino silane to form an effective coverage at the rupture of the carbon coating layer. If the molecular weight of the polyethylene glycol segment is too large, the stability after hydrolysis is poor; if the molecular weight is too small, it will not have an effective shuttle structure; therefore, the molecular weight of the polyethylene glycol segment should be controlled within an appropriate range.
[0013] Furthermore, the in-situ modification is achieved by hydrolyzing epoxysilane, bisaminosilane and bissilane polyethylene glycol, and then sequentially performing a condensation reaction and a cross-linking reaction at a higher temperature with the carbon coating layer in the pre-lithiated silicon-based material containing a carbon coating layer, and then adding 1,3,5-benzenetricarboxylic acid chloride to perform a cross-linking reaction after cooling to room temperature. After in-situ modification of the ruptured carbon coating layer, the carbon coating layer on the surface of the pre-lithiated silicon-based material is repaired by carbonization treatment.
[0014] Furthermore, the silicon-based material is at least one of silicon dioxide, silicon monoxide, magnesium silicate, lithium silicate, sodium silicate, potassium silicate and calcium silicate; and the particle size of the silicon-based material is 3 to 8 μm.
[0015] Furthermore, the thickness of the carbon coating layer is 3 to 20 nm, preferably 5 to 15 nm.
[0016] Furthermore, the pre-lithiation lithium source is one of lithium, lithium carbonate, lithium hydroxide, lithium hydride, and lithium borohydride, and the lithium source is 8-10wt% of the silicon-based material containing the carbon coating layer.
[0017] In a second aspect, the present invention provides a method for preparing the above-mentioned in-situ repaired silicon-based composite material, comprising the following preparation steps:
[0018] (S1) carbon coating: carbon coating the silicon-based material to obtain a silicon-based material containing a carbon coating layer;
[0019] (S2) pre-lithiation: pre-lithiation the silicon-based material containing the carbon coating layer to obtain a pre-lithiation silicon-based material containing the carbon coating layer;
[0020] (S3) In-situ modification: dispersing the pre-lithiated silicon-based material containing the carbon coating layer in an alcohol aqueous solution to obtain a dispersion; dispersing epoxysilane, bisaminosilane, and bissilane polyethylene glycol in water for hydrolysis to obtain a hydrolysis solution; mixing the hydrolysis solution and the dispersion under an inert atmosphere, stirring the mixture, and then heating the mixture to 70 to 85° C. to continue the reaction; finally, cooling the mixture to room temperature, adding 1,3,5-benzenetricarboxylic acid chloride, and continuing the reaction to obtain a precursor;
[0021] (S4) Carbonization: Carbonizing the precursor at 450-600° C. under an inert atmosphere to obtain an in-situ repaired silicon-based composite material.
[0022] In step (S1), the carbon coating method is well known in the art, such as chemical vapor deposition or solid phase coating; preferably, chemical vapor deposition is used, that is, a gaseous carbon source is chemically vapor deposited on the surface of a silicon-based material to form a carbon coating layer, for example, the gaseous carbon source is selected from at least one of C1-4 alkanes (such as methane, ethane, propane), C2-4 olefins (such as ethylene, propylene, 1-butene), and C2-4 alkynes (such as acetylene, propyne); the process conditions are: 800°C to 1000°C in an inert atmosphere, and the reaction is for 2h to 5h.
[0023] In step (S2), the pre-lithiation method is well known in the art, such as solid-phase pre-lithiation or liquid-phase pre-lithiation. For example, the process conditions for solid-phase pre-lithiation are: after mixing the silicon-based material containing the carbon coating layer with the lithium source, sintering at a temperature of 400-600°C for 5-12 hours. The process conditions for liquid-phase pre-lithiation are: adding the silicon-based material containing the carbon coating layer to a complex solution composed of lithium and polycyclic aromatic compounds, wherein the solvent is an ether; then reacting at a temperature of 30-70°C for 10-24 hours to obtain a slurry with a solid content of 30%-60%; the slurry is then sintered at a temperature of 500-600°C for 5-12 hours.
[0024] Furthermore, in step (S3), the ratio of the silicon-based material of the pre-lithiation carbon-containing coating layer to the alcohol aqueous solution is 100g:(500-1000)mL, the alcohol content in the alcohol aqueous solution is 30-60wt%; the alcohol is at least one of methanol, ethanol, and propanol.
[0025] Furthermore, in step (S3), the ratio of the total amount of epoxysilane, bisaminosilane, and bissilane polyethylene glycol to water is (40-50) g:100 mL; and the conditions of the hydrolysis reaction are: stirring the reaction at room temperature for 20-50 min.
[0026] Furthermore, in step (S3), the stirring reaction conditions are: stirring the reaction at 50-60° C. for 2-6 hours; the continued reaction time is 1-2 hours; and the further continued reaction time is 0.5-1 hour.
[0027] Furthermore, the carbonization time in step (S4) is 4 to 8 hours.
[0028] Furthermore, the inert atmosphere in step (S3) and step (S4) is nitrogen, argon or helium.
[0029] In a third aspect, the present invention provides a repairing agent for a pre-lithiation carbon coating layer, which is a compound of epoxysilane, bisaminosilane, bissilane polyethylene glycol, and 1,3,5-benzenetricarboxylic acid chloride in a mass ratio of 1: (0.5-0.8): (0.1-0.2): (0.01-0.03).
[0030] In a fourth aspect, the present invention provides the use of the above-mentioned repair agent in the repair of the carbon coating layer after pre-lithiation of silicon-based negative electrode materials.
[0031] In a fifth aspect, the present invention provides a lithium battery, wherein the negative electrode thereof comprises the above-mentioned in-situ repaired silicon-based composite material.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The present invention pre-lithiates the carbon-coated silicon-based material, and then uses a composite repair agent composed of epoxysilane, bisaminosilane, disilane polyethylene glycol and 1,3,5-benzenetricarboxylic acid chloride to modify it in situ, and then performs a low-temperature carbonization treatment, thereby forming a dense and stable organic silicon-carbon repair patch at the broken carbon layer. One end of the hydrolyzed epoxysilane, bisaminosilane and disilane polyethylene glycol is a silanol group, which undergoes a condensation reaction with the silanol group at the broken carbon coating layer in the pre-lithiated silicon-based material containing the carbon coating layer, thereby introducing the epoxysilane, bisaminosilane and disilane polyethylene glycol into the broken carbon layer of the precursor by chemical bonds; at the same time, disilane polyethylene glycol is a long-chain bifunctional silane coupling agent, and its long chain segment can complement the short-chain epoxysilane and bisaminosilane to form an effective coverage at the broken carbon coating layer. In addition, when the active epoxy group at the other end of the epoxysilane is heated to 70-85°C in an inert atmosphere, it can undergo a cross-linking reaction with the diamino group of diaminosilane, thereby forming a dense repair patch at the rupture of the carbon layer; 1,3,5-benzenetricarboxylic acid chloride can also undergo a moderate cross-linking reaction with the amino group in diaminosilane to improve the density of the repair patch. Finally, after carbonization, a dense and stable organic silicon-carbon repair patch is formed at the rupture of the carbon layer. The organic silicon-carbon repair patch inhibits the dissolution of lithium silicate from the lithium silicon-based material and avoids the gelation and gas generation of the negative electrode slurry.
[0034] (2) In the process of preparing the silicon-based composite material of the present invention, the organic silicon-carbon repair patch can be carbonized at a temperature of 450 to 600° C. Within this temperature range, the silicon grains do not grow and are in an amorphous state.
[0035] (3) The in-situ modification of the present invention is carried out in a liquid alcohol-water solution, which can have a certain effect on removing the residual alkali on the surface of the lithiated silicon-based material; at the same time, compared with the pure water environment, the alcohol-water solution environment can also inhibit the excessive dissolution of lithium silicates in the lithiated silicon-based material.
[0036] (4) When the silicon-based composite material prepared by the present invention is used as the negative electrode of a lithium battery, it exhibits high first coulombic efficiency and stable cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a schematic structural diagram of the in-situ repair silicon-based composite material prepared by the present invention.
[0038] Figure 2 This is the XRD pattern of the in-situ repaired silicon-based composite material prepared in Example 1.
[0039] Figure 3 This is the first cycle charge and discharge curve of a lithium battery assembled with the in-situ repaired silicon-based composite material prepared in Example 1 at a rate of 0.1C. DETAILED DESCRIPTION
[0040] In order to better explain the present invention, the following description will be given in detail with reference to the embodiments of the present invention, and the main contents of the present invention will be further clarified in conjunction with specific examples. However, the contents of the present invention are not limited to the following examples.
[0041] Unless otherwise specified, the “parts” described in the embodiments of the present invention are all parts by mass, and the reagents used are all commercially available reagents in the art.
[0042] The particle size of silicon dioxide SiO2 is 6.6 μm, and it is selected from Shanxi Fuji New Energy Material Technology Co., Ltd. Silane-PEG400-Silane and Silane-PEG800-Silane are both disilane polyethylene glycol, and the number average molecular weight of the polyethylene glycol segment in Silane-PEG400-Silane is 400, and the number average molecular weight of the polyethylene glycol segment in Silane-PEG800-Silane is 800; both are selected from Guangzhou Carbon Water Technology Co., Ltd.
[0043] Example 1
[0044] (S1) Carbon coating: silicon dioxide is placed in a coating furnace, the temperature is raised to 920° C. under a nitrogen atmosphere, and acetylene gas is introduced at a flow rate of 3 L / min for carbon coating for 2 h to obtain a silicon-based material containing a carbon coating layer;
[0045] (S2) Pre-lithiation: 300 g of carbon-coated silicon-based material was added to a complex solution consisting of 27 g of lithium and 750 ml of biphenyl, wherein the solvent was tetrahydrofuran; then the mixture was reacted at 50° C. for 15 h to obtain a slurry; then the slurry was sintered at 600° C. for 8 h to complete the pre-lithiation and obtain a pre-lithiated silicon-based material containing a carbon coating layer (silicon grain size was 3.6 nm);
[0046] (S3) In-situ modification: 230 g of pre-lithiated silicon-based material containing a carbon coating layer (i.e., the mass ratio of the precursor to the repair agent is 100:7) is dispersed in 2000 mL of ethanol aqueous solution (ethanol content is 50 wt%) to obtain a dispersion; 10 g of (3-glycidoxypropyl)trimethoxysilane, 5 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and 1 g of Silane-PEG400-Silane are dispersed in 40 mL of water, and hydrolyzed at room temperature for 30 min to obtain a hydrolysis solution; the hydrolysis solution is added to the dispersion, stirred and reacted at 60°C for 2 h under nitrogen protection, and then heated to 80°C and continued to react for 1 h; finally, after cooling to room temperature, 0.1 g of 1,3,5-benzenetricarboxylic acid chloride is added and the reaction is continued at room temperature for 0.5 h; then, the precursor is obtained by suction filtration, washing with pure water, and drying in an oven at 60°C for 12 h;
[0047] (S4) Carbonization: The precursor is carbonized at 550° C. for 6 h under a nitrogen atmosphere to obtain an in-situ repaired silicon-based composite material.
[0048] Figure 1 It is a schematic structural diagram of the in-situ repair silicon-based composite material prepared by the present invention.
[0049] Figure 2 This is the XRD diagram of the silicon-based composite material for in-situ repair of silicon obtained in Example 1, from which it can be seen that the XRD crystal form has no impurity peaks; the silicon grain size is calculated to be 3.8 nm through fitting.
[0050] Example 2
[0051] The rest is the same as Example 1, except that, in step (S3), the amount of the silicon-based material of the pre-lithiated carbon-containing coating layer is 134.2 g (that is, the mass ratio of the silicon-based material of the pre-lithiated carbon-containing coating layer to the repair agent is 100:12), and the amount of the ethanol aqueous solution is 1200 mL.
[0052] Example 3
[0053] The rest is the same as Example 1, except that, in step (S3), the amount of the silicon-based material of the pre-lithiated carbon-containing coating layer is 100.6 g (that is, the mass ratio of the silicon-based material of the pre-lithiated carbon-containing coating layer to the repair agent is 100:16), and the amount of the ethanol aqueous solution is 1000 mL.
[0054] Example 4
[0055] The rest is the same as Example 1, except that in step (S3), the amount of the silicon-based material of the pre-lithiated carbon-containing coating layer is 80.5 g (that is, the mass ratio of the silicon-based material of the pre-lithiated carbon-containing coating layer to the repair agent is 100:20), and the amount of the ethanol aqueous solution is 800 mL.
[0056] Example 5
[0057] The rest is the same as Example 2, except that the amount of each material in step (S3) is: 147.5g of pre-lithiated silicon-based material of the carbon-containing coating layer (that is, the mass ratio of the silicon-based material of the pre-lithiated carbon-containing coating layer to the repair agent is 100:12), 10g of (3-glycidoxypropyl)trimethoxysilane, 6g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 1.5g of Silane-PEG400-Silane, and 0.2g of 1,3,5-benzenetricarboxylic acid chloride.
[0058] Example 6
[0059] The rest is the same as Example 2, except that the amount of each material in step (S3) is: 160.8g of pre-lithiated silicon-based material of the carbon-containing coating layer (that is, the mass ratio of the silicon-based material of the pre-lithiated carbon-containing coating layer to the repair agent is 100:12), 10g of (3-glycidoxypropyl)trimethoxysilane, 7g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 2g of Silane-PEG400-Silane, and 0.3g of 1,3,5-benzenetricarboxylic acid chloride.
[0060] Example 7
[0061] The rest is the same as Example 2, except that the amount of each material used in step (S3) is: 169.2g of precursor (i.e., the mass ratio of precursor to repair agent is 100:12), 10g of (3-glycidoxypropyl)trimethoxysilane, 8g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 2g of Silane-PEG400-Silane, and 0.3g of 1,3,5-benzenetricarboxylic acid chloride.
[0062] Example 8
[0063] The rest is the same as Example 1, except that, in step (S3), (3-glycidoxypropyl)methyldiethoxysilane is used instead of (3-glycidoxypropyl)trimethoxysilane, and N-(2-aminoethyl)-3-aminoisobutyldimethylmethoxysilane is used instead of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
[0064] Example 9
[0065] The rest is the same as Example 1, except that in step (S3), Silane-PEG800-Silane is used instead of Silane-PEG400-Silane.
[0066] Comparative Example 1
[0067] The rest is the same as Example 1, except that, in step (S3), the repair agent is a compound of (3-glycidoxypropyl)trimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and 1,3,5-benzenetricarboxylic acid chloride, that is, it does not contain Silane-PEG400-Silane.
[0068] Comparative Example 2
[0069] The rest is the same as Example 1, except that, in step (S3), the repair agent is a compound of (3-glycidoxypropyl)trimethoxysilane, Silane-PEG400-Silane, and 1,3,5-benzenetricarboxylic acid chloride, that is, it does not contain N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.
[0070] Testing and analysis
[0071] 1) Change in silicon grain size: The silicon grain size in the silicon-based material of the pre-lithiated carbon-containing coating layer in Example 1 is 3.6 nm; Figure 2 This is the XRD diagram of the silicon-based composite material for in-situ repair of silicon obtained in Example 1. The fitting calculation shows that the silicon grain size is 3.8nm, which is not significantly larger than the silicon grain size in the pre-lithiated carbon-containing coating silicon-based material, indicating that the in-situ repair process of the present invention will not significantly increase the silicon grain size.
[0072] 2) The silicon-based composite materials prepared in the examples and comparative examples were subjected to the following performance tests:
[0073] Charge and discharge test: The prepared silicon-based composite material, carbon black and polyacrylic acid (PAA) aqueous solution binder are mixed in a mass ratio of 80:10:10 to form a slurry (wherein the concentration of the polyacrylic acid aqueous solution is 3.4wt%), and the slurry is evenly coated on the copper foil current collector with a certain thickness, and vacuum dried for 12 hours to form a working electrode; lithium sheet is used as the counter electrode, ceramic diaphragm, Shenzhen Xinzhoubang electrolyte, and button cells are assembled in an argon atmosphere Micairon inert gas glove box. The above-assembled battery is charged and discharged on the LAND charge and discharge tester. Test conditions: the charge and discharge range is 0.005-1.5V, and a three-stage discharge method is used. The discharge current density is 0.1C, 0.02C, and 0.01C, respectively, and the charging current density is 0.1C.
[0074] Figure 3 This is the first cycle charge and discharge curve of a lithium battery assembled with the in-situ repaired silicon-based composite material prepared in Example 1 at a rate of 0.1C.
[0075] The high-temperature gas production test method is as follows: the prepared silicon-based composite material, carbon black and sodium carboxymethyl cellulose (CMC) are mixed with styrene-butadiene rubber (SBR) composite binder in a mass ratio of 90:5:5 to form a slurry (wherein the mass ratio of CMC and SBR is 2:3) and packaged into a slurry using an aluminum-plastic bag to exclude air. The initial slurry density value is tested using a solid densitometer, and then the slurry is stored at 45°C for 24 hours and the density value is tested again. The gas production of the material is calculated according to v=m / ρ. The higher the gas production value, the more serious the material damage and the worse the material stability.
[0076] The test results are shown in Table 1.
[0077] Table 1 Performance test
[0078]
[0079] It can be seen from the data in Table 1 that when the silicon-based composite material prepared in the embodiment of the present invention is used as the negative electrode of a lithium battery, its first reversible specific capacity reaches 1400mAh / g, the first coulombic efficiency reaches more than 90%, and the capacity retention rate after 100 cycles reaches more than 75%; in the process of preparing the negative electrode slurry, the gas production of the slurry is low, all lower than 0.2ml / g.
[0080] The above is an explanation of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A silicon-based composite material for in-situ repair, characterized in that: The invention is obtained by in-situ modification of a silicon-based material of a pre-lithiated carbon-containing coating layer with a repair agent, and then carbonization at 450-600°C to form an organic silicon-carbon repair patch; the repair agent is a compound of epoxysilane, bisaminosilane, bissilane polyethylene glycol, and 1,3,5-benzenetricarboxylic acid chloride in a mass ratio of 1: (0.5-0.8): (0.1-0.2): (0.01-0.03); the mass ratio of the silicon-based material of the pre-lithiated carbon-containing coating layer to the repair agent is 100: (7-20).
2. The in-situ repair silicon-based composite material according to claim 1, characterized in that: The repair agent is a compound of epoxy silane, bisamino silane, bissilane polyethylene glycol and 1,3,5-benzenetricarboxylic acid chloride in a mass ratio of 1: (0.6-0.7): (0.15-0.2) (0.02-0.03).
3. The in-situ repair silicon-based composite material according to claim 1, characterized in that: The mass ratio of the silicon-based material of the pre-lithiated carbon-containing coating layer to the repair agent is 100:(12-16).
4. The in-situ repair silicon-based composite material according to claim 1, characterized in that: The epoxysilane is at least one of (3-glycidoxypropyl)trimethoxysilane, (3-glycidoxypropyl)triethoxysilane, (3-glycidoxypropyl)methyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; and / or The bisaminosilane is at least one of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, and N-(2-aminoethyl)-3-aminoisobutyldimethylmethoxysilane; and / or The number average molecular weight of the polyethylene glycol segment in the bisilane polyethylene glycol is 400-800, that is, the number average molecular weight of the PEG segment is 400-800.
5. The in-situ repair silicon-based composite material according to claim 1, characterized in that: The in-situ modification is achieved by hydrolyzing epoxysilane, bisaminosilane and bissilane polyethylene glycol, and then sequentially performing a condensation reaction and a temperature-raising cross-linking reaction with the carbon coating layer in the silicon-based material of the pre-lithiated carbon-containing coating layer, and then adding 1,3,5-benzenetricarboxylic acid chloride to perform a cross-linking reaction after cooling to room temperature.
6. The in-situ repair silicon-based composite material according to claim 1, characterized in that: The silicon-based material is at least one of silicon dioxide, silicon monoxide, magnesium silicate, lithium silicate, sodium silicate, potassium silicate and calcium silicate, and the particle size of the silicon-based material is 3 to 8 μm; and / or The thickness of the carbon coating layer is 3 to 20 nm; and / or The pre-lithiation lithium source is one of lithium, lithium carbonate, lithium hydroxide, lithium hydride, and lithium borohydride, and the lithium source is 8-10wt% of the silicon-based material containing the carbon coating layer.
7. The method for preparing the in-situ repaired silicon-based composite material according to any one of claims 1 to 6, characterized in that: The method comprises the following preparation steps: (S1) carbon coating: carbon coating the silicon-based material to obtain a silicon-based material containing a carbon coating layer; (S2) pre-lithiation: pre-lithiation the silicon-based material containing the carbon coating layer to obtain a pre-lithiation silicon-based material containing the carbon coating layer; (S3) In-situ modification: dispersing the pre-lithiated silicon-based material containing the carbon coating layer in an alcohol aqueous solution to obtain a dispersion; dispersing epoxysilane, bisaminosilane, and bissilane polyethylene glycol in water for hydrolysis to obtain a hydrolysis solution; mixing the hydrolysis solution and the dispersion under an inert atmosphere, stirring the mixture, and then heating the mixture to 70 to 85° C. to continue the reaction; finally, cooling the mixture to room temperature, adding 1,3,5-benzenetricarboxylic acid chloride, and continuing the reaction to obtain a precursor; (S4) Carbonization: Carbonizing the precursor at 450-600° C. under an inert atmosphere to obtain an in-situ repaired silicon-based composite material.
8. The preparation method according to claim 7, characterized in that: In step (S3), the ratio of the silicon-based material of the pre-lithiation carbon-containing coating layer to the alcohol aqueous solution is 100g: (500-1000)mL, the alcohol content in the alcohol aqueous solution is 30-60wt%; the alcohol is at least one of methanol, ethanol, and propanol; and / or The total amount of epoxysilane, bisaminosilane, and bissilane polyethylene glycol used in the reaction is in the ratio of (40-50) g to 100 mL of water; the conditions for the hydrolysis reaction are: stirring the reaction at room temperature for 20-50 min; and / or The stirring reaction conditions are: stirring the reaction at 50-60° C. for 2-6 hours; the continued reaction time is 1-2 hours; and the further continued reaction time is 0.5-1 hour.
9. A repair agent for a pre-lithiated carbon coating layer, characterized in that: It is a compound of epoxy silane, bisamino silane, bissilane polyethylene glycol and 1,3,5-benzenetricarboxylic acid chloride in a mass ratio of 1: (0.5-0.8): (0.1-0.2): (0.01-0.03).
10. A lithium battery, characterized in that: The negative electrode comprises the in-situ repaired silicon-based composite material according to any one of claims 1 to 6.
Citation Information
Patent Citations
High-stability silicon-based negative electrode material and preparation method and application thereof
CN116504955A
